Pengaruh Senam Yoga Hatha terhadap Keluhan Muskuloskeletal pada Ibu Rumah Tangga di Desa Sindon, Ngemplak, Boyolali - Widiarso, Zalfa Afifah Putri; Kurnia, Rina (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Musculoskeletal disorders (MSDs) are complaints caused by persistent collisions, both minor and large, that accumulate over a long period, causing pain and discomfort in muscles, bones, and joints. Hatha yoga is a complementary therapy that can reduce pain, especially in joint pain. Objectives: The purpose of this study was to determine the effect of hatha yoga gymnastics on musculoskeletal complaints in housewives in Sindon Village, Ngemplak, Boyolali. Methods: This study used a pre-experimental design with one group pre-test and post-test design. Sampling using purposive sampling as many as 30 samples. The study variables were measured using the Nordic Body Map (NBM). Hatha yoga exercises are carried out in as many as 12 sessions in 4 weeks. Data analysis using SPSS 23 with Wilcoxon test statistical technique. Results: This study used a pre-experimental design with one group pre-test and post-test design. Sampling using purposive sampling as many as 30 samples. The study variables were measured using the Nordic Body Map (NBM). Hatha yoga exercises are carried out in as many as 12 sessions in 4 weeks. Data analysis using SPSS 23 with Wilcoxon test statistical technique.Conclusion: There is an influence of hatha yoga on musculoskeletal complaints in housewives in Sindon Village, Ngemplak, Boyolali Keywords: Hatha Yoga Gymnastics, Musculoskeletal Complaints, Housewives